Comparative Evaluation of GNSS Positioning Accuracy Using RTK Techniques and CORS-Based Post-Processing Solutions - Aroge, S. K.; Adewole, B. E.; Odeyemi, F. G.; Suru, W. P.; Ayinla, T. A.; Raufu, I. O. (Journal of Spatial Information Sciences, 2025)
Global Navigation Satellite System (GNSS) applications in Osun State, Nigeria, are limited by poor positional accuracy, particularly in vertical measurements. With the recent establishment of a Continuously Operating Reference Station (CORS) by private surveyors, it is important to assess the performance of real-time and post-processed GNSS solutions for local survey practice. This study compared two real-time kinematic (RTK) connection methods: radio frequency (RF) and network RTK via internet (NRTK) with static precise positioning using Canadian Spatial Reference System Precise Point Positioning (CSRS-PPP) and Osun CORS RINEX data processed in South Geomatics Office software. Field data were collected on three control stations with a Tersus Oscar GNSS receiver, and accuracy was evaluated using root mean square error (RMSE) against published control coordinates. Results show that CSRS-PPP (0.11 m easting, 0.17 m northing, 3.78 m height) and Osun CORS (0.09 m easting, 0.11 m northing, 3.76 m height) achieved horizontal accuracies within the allowable 0.05-0.50 m limit, but vertical errors exceeded the 0.10 m tolerance. NRTK (0.06 m easting, 0.03 m northing) performed better than RF-RTK (0.53 m easting, 1.29 m northing) for horizontal positioning, yet both produced unacceptable vertical errors of 24.14 m and 8.54 m, respectively. The findings confirm that online PPP and internet-based RTK provide reliable horizontal accuracy in Osun State, but vertical accuracy remains inadequate and requires further methodological improvement.
Keywords: CORS; GNSS; GNSS-PPP; RTK GNSS; Static Observation